2019
DOI: 10.7160/aol.2019.110403
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Current Support of E-marketing Activities in Selected Enterprises of the Wine Sector in Slovakia

Abstract: In the digital era, implementing an effective marketing strategy requires a more comprehensive view of the marketing strategy than in the past. The concepts of older approaches are already ineffective today, but we consider it important to mention them. Organizations focus on improving production, achieving low cost and mass distribution. The product concept is based on the conviction of consumers who prefer products with the highest quality or innovative characteristics. Managers focus on producing quality pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…FB identity is understood as a firm self-concept, embracing the idiosyncratic attributes resulting from kin-ownership (Nikodemska-Wolowik, 2006;Botero et al 2013;Blombäck & Ramírez-Pasillas, 2012). Concerning market communication, explicit signals are more effective than indirect messages (Hartnett et al, 2016), furthermore, the possibilities of their effective usage increase significantly in terms of intensive ICT development (Bilan, Mishchuk, Samoliuk, & Grishnova, 2019;Janšto, Polakovič, Hennyeyová, & Slováková, 2019;Botos, Szilágyi, Felföldi, & Tóth, 2020;). According to Zanon et al (2019), a large number of FBs worldwide explicitly communicate their family status to stakeholders, but there are countries like Poland, in which consumers are not always able to identify themselves as familyowned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…FB identity is understood as a firm self-concept, embracing the idiosyncratic attributes resulting from kin-ownership (Nikodemska-Wolowik, 2006;Botero et al 2013;Blombäck & Ramírez-Pasillas, 2012). Concerning market communication, explicit signals are more effective than indirect messages (Hartnett et al, 2016), furthermore, the possibilities of their effective usage increase significantly in terms of intensive ICT development (Bilan, Mishchuk, Samoliuk, & Grishnova, 2019;Janšto, Polakovič, Hennyeyová, & Slováková, 2019;Botos, Szilágyi, Felföldi, & Tóth, 2020;). According to Zanon et al (2019), a large number of FBs worldwide explicitly communicate their family status to stakeholders, but there are countries like Poland, in which consumers are not always able to identify themselves as familyowned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of the pandemic and lockdown some professions experienced more than a 100% boost, among them e-marketing and delivery services. E-marketing in particular proves to be an important element of the new business relations (Anser et a., 2020;Janšto et al, 2019) and it showed itself as very useful during the recent crisis.…”
Section: Human Resources and Personnel Security During Lockdownsmentioning
confidence: 99%
“…The agricultural sector in Indonesia plays a crucial role in the overall economic development of the country (Belete, 2022;Bromley, 2009;Hayden et al, 2022;Saygılı & Çakmak, 2022;Tripoli & Schmidhuber, 2018). It serves as a significant source of employment, particularly in rural areas, and contributes to the livelihoods of millions of people (Armoogum et al, 2016;Janšto et al, 2019;MacUra et al, 2019;Siddiqui, 2018). Moreover, it plays a vital role in ensuring food security for the growing population of Indonesia.…”
Section: Introductionmentioning
confidence: 99%